The balance between pro‐ and anti‐inflammatory cytokines is crucial in human allergic contact dermatitis pathogenesis: the role of IL‐1 family members. Issue 12 (December 2013) - Mattii, Martina; Ayala, Fabio; Balato, Nicola; Filotico, Raffaele; Lembo, Serena; Schiattarella, Maria; Patruno, Cataldo; Marone, Gianni; Balato, Anna
Abstract The interleukin (IL)‐1 family includes 11 members that are important in inflammatory processes. It includes various agonists and two antagonists, IL‐1Ra and IL‐36Ra. Our aim was to investigate whether the IL‐1 family is involved in allergic contact dermatitis (ACD). The expression of IL‐1 family members was evaluated by PCR and immunohistochemistry in the positive patch test reaction site (involved skin) and in the uninvolved skin of ACD patients. We also examined these cytokines in an ex vivo model of ACD. The antagonistic activity of IL‐36Ra was evaluated by injecting recombinant IL‐36Ra in uninvolved skin biopsies of ACD patients. IL‐1Ra and IL‐36Ra expression was quantified in mononuclear cells of nickel‐sensitized patients challenged in vitro with nickel. IL‐33 involvement in ACD was investigated by intra‐dermal injection of anti‐IL‐33 in the uninvolved skin of patients ex vivo. Results showed that IL‐1β, IL‐1Ra, IL‐36α, IL‐36β, IL‐36γ and IL‐33 expression, but not IL‐36Ra expression, was enhanced in ACD‐involved skin. Immunohistochemical analysis and ex vivo skin cultures confirmed these results. Injection of anti‐IL‐33 in ACD‐uninvolved skin inhibited IL‐8 expression, whereas IL‐36Ra inhibited IL‐36α, IL‐36β, IL‐36γ and IL‐8 expression. Nickel induced IL‐1Ra expression in lymphocytes of nickel‐sensitized patients. Hence, various IL‐1 agonists and antagonists may be involved in ACD pathogenesis.